Factors associated with polypharmacy in geriatrics - Rathod, Geeta; G. K., Nalini; Nagaral, Jayashree V.; G. N., Sahana; P., Deepak; Prema, M.; U. S., Nuthan Kumar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: In population with advancing age, the prevalence of medical co-morbid conditions is high and they are prone for complications. Hence the apprehension of using multiple drugs is more. Using more than 5 drugs per day is referred to as Polyphrmacy. Sometimes treatment causes more harm than the disease proper. So, optimizing drug therapy in these aging population is a challenging task for physician. Polypharmacy can also lead to increase in drug interactions, adverse drug reactions and medication errors. Hence the present study was taken up to study drug utilization pattern and factors leading to polypharmacy in geriatrics. The objectives of the study were to study the number and type of drug use and to know the different factors leading to polypharmacy. Methods: Cross sectional study was carried out among 60 geriatric persons ≥60 years of age present in old age home in Hassan. The study was done after taking the consent. All the prescriptions and medications being used along with history were collected and documented. The total number of drugs being used and names of all drugs were noted down and analysed. Results were analysed using descriptive statistics. Results: Among 60 geriatrics 38% males and 62% females age ranges from 60- 87 years. Average number of drugs used per day per person is 5.03 (Males 6.2 and Females 3.8) in 58.03% of individuals. Most common group of drug used is Gastro intestinal system (78.3%) and most common drug being used is Tab. Ranitidine 140mg (50%). Next group is NSAIDs (68.33%) and most common drug being used is Tab. Diclofenac (46.7%). Antihypertensive drugs were prescribed in 53.3% of geriatrics, most commonly prescribed drug is Tab. Amlodipine (5mg). Self medication was found in 100%. Most common group of drugs used as self medication are GIT drugs, supplements and NSAIDs. In supplements (used in 63.3%), Cap. B Complex is widely used (50%). Conclusions: Polypharmacy was found in 58.3% of individuals and highest in age group between 71-75 years and self medication was found to be the most important factor leading to polypharmacy. To counteract the problems associated with Polypharmacy, interventional studies are needed to improve the quality of life of geriatrics patients.